A New Reaction of Isatin, Cyclic 1, 3‐Diketone, and 2‐Cyanoacetamide: A Four‐Component Synthesis of Spirooxindoles. (29th March 2013) - Ghahremanzadeh, Ramin; Hosseini, Ghaffar; Akbarzadeh, Roya; Bazgir, Ayoob
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>